Reaction of monosilane with ammonia at low pressure I. Mathematical model of the process of deposition of silicon nitride films - "Popov, V P"; "Ginovker, A S"; "Vasil'eva, L L" (1981)
Deposition of silicon nitride films was studied under steady-state conditions at 850 /sup 0/C and a pressure of 1.2.10/sup 2/ Pa. It is assumed that the reaction in the gas phase appears as the limiting step of the processes. A mathematical model was formulated for the process within the framework of which the deposition rate profile is determined by the geometry of the reaction space.
Keywords: "37 INORGANIC, ORGANIC, PHYSICAL AND ANALYTICAL CHEMISTRY"; "36 MATERIALS SCIENCE"; "SILICON NITRIDES"; "CHEMICAL REACTION KINETICS"; "DEPOSITION"; "AMMONIA"; "FILMS"; "LOW PRESSURE"; "MATHEMATICAL MODELS"; "STEADY-STATE CONDITIONS"; "VERY HIGH TEMPERATURE"; "HYDRIDES"; "HYDROGEN COMPOUNDS"; "KINETICS"; "NITRIDES"; "NITROGEN COMPOUNDS"; "NITROGEN HYDRIDES"; "PNICTIDES"; "REACTION KINETICS"; "SILICON COMPOUNDS"; "400201* - Chemical & Physicochemical Properties"; "360202 - Ceramics, Cermets, & Refractories- Structure & Phase Studies"